Tunable photoluminescence emissions and large dielectric constant of the electroactive poly(vinylidene fluoride–hexafluoropropylene) thin films modified with SnO2 nanoparticles. Issue 36 (22nd March 2016) - Hoque, Nur Amin; Thakur, Pradip; Bala, Niranjan; Kool, Arpan; Das, Sukhen; Ray, Partha Pratim
Abstract : Fabrication of optically active, electroactive and percolative SnO2 NPs/PVDF–HFP nanocomposite thin films with remarkable dielectric constants. Abstract : In the present study, SnO2 nanoparticles (NPs) have been synthesized hydrothermally at 100 °C and 150 °C. The NPs have been characterized by X-ray diffraction (XRD), UV-visible spectroscopy and field emission scanning electron microscopy (FESEM). Thereafter, poly(vinylidene fluoride–hexafluoropropylene) (PVDF–HFP) with different contents (1–15 wt%) of SnO2 NPs has been synthesized by a simple solution-casting method. An electroactive β-phase formation mechanism in the NP-incorporated PVDF–HFP thin films is confirmed by XRD, Fourier transform infrared spectroscopy and differential scanning calorimetry. FESEM images show interfacial interaction in the thin films between the polymer matrix and the NPs. Maximum β-phase nucleation of ∼74% has been reached by 10 wt% addition of SnO2 NPs synthesized hydrothermally at 100 °C. The photoluminescence emission spectra show two UV and visible emissions at two excitation wavelengths. Uniform distribution of the NPs in the polymer matrix leads to large dielectric constant ∼2578.44 at 20 Hz due to addition of 10 wt% SnO2 NPs (100SO) in PVDF–HFP matrix. The large increase in dielectric constant has been successfully explained in terms of MWS polarization effect and percolation theory.